Expansion of HIV testing in Eswatini: stakeholder perspectives on reaching the first 90 - Kitchen, Philip J.; Bärnighausen, Kate; Dube, Lenhle; Mnisi, Zandi; Dlamini-Nqeketo, Sithembile; Johnson, Cheryl C.; Bärnighausen, Till; De Neve, Jan-Walter; McMahon-Rössle, Shannon A. (African journal of AIDS research, 2020)
Achieving the United Nations’ 90-90-90 goals has proven challenging in most settings and the ambitious 95-95-95 goals seem even more elusive. However, in Eswatini - a lower-middle-income country in sub-Saharan Africa with the highest HIV prevalence in the world - an estimated 92% of people living with HIV know their status. We conducted 26 in-depth interviews with stakeholders from policy, implementation, donor, local advocacy and academic sectors to elicit the facilitators and inhibitors to HIV testing uptake in Eswatini. Background data and related reports and policy documents (n = 57) were also reviewed. Essential facilitators included good governance via institutional and national budgetary commitments, which often led to swift adoption of globally recommended programs and standards. The integration of HIV testing into all points of care fostered a sense that testing was part of routine care, which reduced stigma. Challenges, however, centred on social norms that disadvantage certain groups with high ongoing HIV risk (such as key populations, adolescent girls and young women), a heavy reliance on external donor funding, and stigma that had subsided but nevertheless persisted. Amid concerns about whether the 90-90-90 targets could be achieved by 2020, the experience of Eswatini provides tangible insights into factors that have successfully influenced HIV testing uptake and may thus prove informative for other countries.
Gesehen am 17.12.2020